2018
DOI: 10.1159/000492123
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Intravenous Thrombolysis in Patients with Minor Stroke

Abstract: Background: The actions and responses of the hospital personnel during acute stroke care in the emergency department (ED) may differ according to the severity of a patient’s stroke symptoms. We investigated whether the time from arrival at ED to various care steps differed between patients with minor and non-minor stroke who were treated with intravenous tissue plasminogen activator (IV tPA). Methods: We included consecutive patients who received IV tPA during a 1.5 year-period in 5 hospitals. Minor stroke was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Our findings are clinically relevant due to the substantial number of tPA‐eligible AIS patients precluded from IVT only because of mild symptoms at hospital admission [28,29] and the possibility of neurological deterioration during the first hours of hospitalization in patients with AIS due to large vessel occlusions [30,31]. Also taking into account the increased delays in IVT administration for AIS patients with mild neurological deficits on admission [32‐34] and the inverse relationship between onset to bolus time and functional improvement in AIS patients with large vessel occlusions [35], prompt tPA delivery for these patients appears to be crucial for their outcome independent of their eligibility for MT. The lack of difference in 3‐month functional outcomes according to MT treatment highlighted in our report (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are clinically relevant due to the substantial number of tPA‐eligible AIS patients precluded from IVT only because of mild symptoms at hospital admission [28,29] and the possibility of neurological deterioration during the first hours of hospitalization in patients with AIS due to large vessel occlusions [30,31]. Also taking into account the increased delays in IVT administration for AIS patients with mild neurological deficits on admission [32‐34] and the inverse relationship between onset to bolus time and functional improvement in AIS patients with large vessel occlusions [35], prompt tPA delivery for these patients appears to be crucial for their outcome independent of their eligibility for MT. The lack of difference in 3‐month functional outcomes according to MT treatment highlighted in our report (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although age, vascular risk factors other than dyslipidemia, and occlusion site did not change over time, stroke severity slightly decreased. This may be ascribed to the increase in reperfusion therapy for minor stroke and decrease in the prevalence of atrial fibrillation-or atrial flutter-related stroke [20,21]. Furthermore, time from stroke onset to ED was longer than those in previous studies because patient eligibility for EVT might be based more on imaging parameters recently, instead of the time window paradigm [22].…”
Section: Discussionmentioning
confidence: 99%
“…There were numerous possibilities to explain why more patients with non-disabling stroke (NIHSS ≤4) during the post-intervention group. Previous studies showed longer DNT in patients with minor stroke, possibly due to higher chance of atypical symptoms, delayed neurology notification and diagnosis [23,24]. The early diagnosis and decision making from better implementation of the Stroke: Target strategies in the postintervention group would naturally increase IVT for patients with minor strokes.…”
Section: Discussionmentioning
confidence: 99%